First record of Typhlodromus (Anthoseius) transvaalensis (Acari: Phytoseiidae) from Argentina - Cédola, Claudia Viviana; Castresana, Jorge Eduardo (Sociedad Entomológica Argentina, 2021)
We report for the first time from Argentina Typhlodromus (Anthoseius) transvaalensis Nesbitt from Capsicum annuum L. and Lycopersicum esculentum L. (Solanaceae) in Concordia, Entre Ríos. Morphometric parameters of Argentine specimens are provided.